Multivariate Analysis of Drivers of Migration, Challenges, and Prediction of Future Scenarios of Female Ethiopian Return Migrants From the Middle East - Ebrahim, Endris Assen; Biru, Belay Zeleke (Frontiers in Applied Mathematics and Statistics, 2022)
The migration of Ethiopians to Middle Eastern countries has become a common phenomenon. Research emphasizing aspects of migration in Ethiopia has focused on the causes of migration and the situation in the host country. But none on future intentions of forced mass return. The internal instability of Ethiopia is also another issue for returnees staying in their homeland. Thus, this cross-sectional mixed research reveals the causes, challenges, and expectations of forced female returnee migrants in the Amhara region while they were in migration to the Middle East, during work, and upon arrival to the homeland, as well as their future intention/plan/ after return in the homeland by applying factor analysis and binary logistic regression model. The study participants in this research were 346 forced female returnees from the Middle East selected with multistage sampling, and 2 key informants from each study area's labor and social affairs office. Findings indicate that robbery and extortion, and lack of accommodation were challenges during migration; verbal abuse, restricted mobility, and communication, no day off at work, and not receiving a wage for work were challenges during work in the Middle East. Besides, lack of happiness, lack of employment and support, and feeling inferiority and low self-esteem are challenges for return migrants after coming to their homeland. Most of the return migrants were getting continuous social counseling training, skill training, and entrepreneurship training. The study also reveals that currently married returnees have a positive significant intention to live in their homeland. Though, deprived, economic factors and joblessness-related factors are statistically significant as the negative chance to live in the homeland. Lastly, the study recommends that close cooperation between all parties, governmental and non-governmental institutions, UN organizations like IOM, ILO, and other NGOs are needed for the better reintegration and living of these forced returnees.